Multipoint boundary-value problems with pulse effects - Karandjulov, L.I. (Український математичний журнал, 1995)
By using pseudoinverse matrices, we establish conditions for the existence and uniqueness of solutions of linear and weakly linear boundary-value problems for ordinary differential equations with pulse action. We consider the case where the dimension of a differential system does not coincide with the dimension of the boundary conditions. На основі псевдообернених матриць одержані умови існування та єдиності розв’язків лінійних та слабкоиелінійних крайових задач для звичайних диференціальних рівнянь з імпульсною дією. Розглянуто випадок, коли розмірність диференціальних систем і розмірність крайових умов не співпадають.